In-situ 3D fouling visualization of membrane distillation treating industrial textile wastewater by optical coherence tomography imaging. (15th October 2021) - Wong, Pak Wai; Guo, Jiaxin; Khanzada, Noman Khalid; Yim, Vicki Man Wai; Kyoungjin, Alicia
Highlights: Successfully visualized separation of fouling layer from a single 3D OCT image. Observed thin and disperse fouling growth through analysis of 3D OCT imagery. Quantitatively analyzed the fouling index to compare membrane antifouling ability. Analyzed the effect of surface energy on the interaction with foulant particles. Abstract: Membrane fouling, which is caused by the deposition of particles on the membrane surface or pores, reduces system performance in membrane distillation (MD) applications, resulting in increased operational costs, poor recovery, and system failure. Optical Coherence Tomography enables in-situ foulant monitoring in both 2D and 3D, however, the 2D images can only determine fouling layer thickness in severe fouling. Therefore, in this study, an advanced 3D imaging analysis technique using intensity range filters was proposed to quantify fouling layer formation during MD through the use of a single 3D image. This approach not only reduces computational power requirements, but also successfully separated the fouling layer from the membrane at the microscale. Thus, the thickness, fouling index, and fouling layer coverage can be evaluated in real time. To test this approach, Polyvinylidene fluoride (C-PVDF) and polytetrafluoroethylene (C-PTFE) membranes were used to treat a feed consisting of industrial textile wastewater. Thin and disperse foulants was observed on the C-PTFE, with a 22 µm thick fouling layer which could not be observed using 2D images after 24 h. Moreover, the C-PTFE demonstrated better antifouling ability than the C-PVDF as demonstrated by its lower fouling index, which was also supported by surface energy characterization. This work demonstrates the significant potential of 3D imagery in the long-term monitoring of membrane fouling process to improve membrane antifouling performance in MD applications, which can lead to lowered operational costs and improved system stability. Graphical abstract: Image, graphical abstract